Is it profitable to trade solely upon financial narratives? : portfolio creation based on textual analysis - Gouveia, Diogo António Evangelista (2024)
The research aims to understand if profitability can be achieved relying solely on textual analysis metrics, such as word count, Flesch score, Fog index, causal reasoning, forward-looking indicators, uncertainty, and net tone. The characteristics of financial narratives were examined across three different sections of the annual report, the entire document, the Chairman's and the CEO's statements. Ten portfolios for each characteristic were constructed with equal weighting of short and long positions, determined by the top and bottom performers identified within the narrative, based on the literature available. However, findings indicate that, based on the portfolio construction criteria, exclusive dependence on narrative measures is not a viable approach for achieving profitability and mostly leads to value erosion.